The design of manmade water stream and landscape for water conservation and community project development / Fong Mei Yong - Fong , Mei Yong (2021)
This study is for the water conservation and community development project in Rumah Hutan Jeram. In this project, we had proposed a design of the manmade water stream and the landscape design of the Rumah Hutan Jeram. To come out with the design plan and idea, we will first need to determine the water source for the manmade water stream. We had identified the groundwater potential ranking using the GIS methods and estimate the groundwater recharge rate. From the geological data and the remote sensing data, it had shown that the Rumah Hutan Jeram area is high groundwater potential. On the other hand, the groundwater recharge rate is in between 247mm - 265 mm. These data had shown that the existing borewell is sufficient to support the water stream. This project analysed the designed and planned of the manmade water stream and the surrounding landscape with the aid of Geographical Informative System (GIS) and Remote Sensing. Rumah Hutan Jeram was designed according to the theme of natural and sustainable concept. This research project has some important criteria and adheres to the concept of water and energy conservation. In this research, the risk assessment and control measure were also included, and it is suggested according to the landscaping construction activities.